2021
DOI: 10.1080/00207543.2021.1946194
|View full text |Cite
|
Sign up to set email alerts
|

Transdisciplinary perspective on sustainable multi-tier supply chains: a triple bottom line inspired framework and future research directions

Abstract: Global sourcing and increased interdependencies between organisations have created more complex multi-tier supply chains. While these supply chains have been instrumental in keeping the world moving, they equally pose sustainability issues. In the extant literature, there is a growing number of studies on sustainable multi-tier supply chains. However, there has been limited effort to take stock of existing research to set an agenda for future studies. To address this gap, this study reviews 64 articles through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 85 publications
0
14
0
2
Order By: Relevance
“…One sustainability strategy is an accounting framework called the triple bottom line, aimed at improving economic, environmental and social performance through innovation, communication and product value (Chen and Huang, 2018). Economic performance relates to customer value and cost efficiency to produce profit; environmental performance integrates environmental goals to reduce waste and conserve natural resources; social performance includes product and process-related operations that improve human capital (Senyo and Osabutey, 2021). The common goal among the three dimensions of the triple bottom line is to enhance stakeholder value through improving the performance of brand offerings and the related operations (Elkington, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One sustainability strategy is an accounting framework called the triple bottom line, aimed at improving economic, environmental and social performance through innovation, communication and product value (Chen and Huang, 2018). Economic performance relates to customer value and cost efficiency to produce profit; environmental performance integrates environmental goals to reduce waste and conserve natural resources; social performance includes product and process-related operations that improve human capital (Senyo and Osabutey, 2021). The common goal among the three dimensions of the triple bottom line is to enhance stakeholder value through improving the performance of brand offerings and the related operations (Elkington, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The triple bottom line approach to sustainability is distinct because it: emphasizes revenue generation; is concerned with internal processes and innovation; and encompasses the ideology that firms should make concerted efforts to simultaneously address all three dimensions (Senyo and Osabutey, 2021). …”
Section: Introductionmentioning
confidence: 99%
“…Wilhelm et al (2016a) concluded that future research should focus on the effects of power asymmetries in multi-tier supply chains and that the issue should be investigated in the empirical context of different industries. More empirical research on multi-tier supply chains has also been called for by Senyo and Osabutey (2021), who stated that rigorous studies that validate the results in multiple sectors and countries are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Shifting demands of consumers, investors, trade associations, and governments have increased the pressure on global brands to demonstrate adherence to social and environmental standards (López Sarabia et al, 2021; Mohua & Yusoff, 2021; Phillips et al, 2018). At the same time, apparel and manufacturing supply chains are characterised by highly complex multi‐tier supply chains, which pose significant sustainability monitoring challenges (Senyo & Osabutey, 2021). Multi‐tier apparel supply chains take many shapes and include a variety of structural arrangements of relationships between consumers, buyers, suppliers, and supplier's suppliers (Mena et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent literature review of sustainable multi‐tier supply chains proposes a framework of social and environmental objectives that relies on integration of assessment approaches and the regular monitoring of supply chain actors to identify emerging issues (Senyo & Osabutey, 2021). Third party social audits are intended to monitor and communicate compliance to stakeholders (Hannibal & Kauppi, 2019).…”
Section: Introductionmentioning
confidence: 99%